Development of a questionnaire to measure primary care physicians' scope of practice. Issue 1 (December 2015) - Ie, Kenya; Ichikawa, Shuhei; Takemura, Yousuke
Abstract Background Despite an increase in research devoted to primary care attributes, the patient benefits and educational aspects of broad scope practice of primary care physicians (PCPs) have not been well studied, due to a lack of validated measurement in each country. The objective of this study was to develop and validate the Scope of Practice Inventory (SPI) to measure physicians' scope of practice within the Japanese primary care setting. Methods The questionnaire was developed in seven phases: 1) item generation, 2) consensus method for necessity of each item, 3) Delphi process for the importance of each item, 4) pilot tests to limit the number of items, 5) preliminary cross-sectional study to examine factor structure and to validate the construct validity, 6) evaluation of internal consistency and intra-class reliability, and 7) evaluation of external validity. To confirm the interpretability of the SPI, the determinants of the SPI using a generalized linear model were evaluated. Results Among 359 items generated by a focus group, 180 reached a defined consensus on face and content validity after the Delphi process. After deletion of items with Kappa values less than 0.6, 120 items were selected for the preliminary study. The principle component analysis using responses from 451 PCPs eliminated 52 items. The final 68-point SPI had three subdomains: Inpatient care, 25 items; Urgent care and minor procedures, 27 items; and Ambulatory care, 16 items. Internal consistency and test-retest reliability for total SPI and each subdomain revealed acceptable reliability. Male sex, less years since graduation, working in a hospital, sub-urban or rural setting, having remote experience, and having board certification as a PCP were positively associated with higher SPI. Conclusions We developed a self-administered 68-point scale, the SPI, which had satisfactory validity and reliability. Primary care quality and educational research using SPI are expected to contribute to comprehensive and efficient health care systems in the future.